The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/nu8100624
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dietary Vitamin A and Carotenes and the Risk of Primary Liver Cancer: A Case–Control Study

Abstract: Dietary intake of vitamin A (VA) and carotenes has shown beneficial effects for decreasing the risk of some types of cancer, but findings on the risk of primary liver cancer (PLC) are inconsistent. This case–control study explored the associations between the dietary intake of VA and carotenes and the risk of PLC. We recruited 644 incident PLC patients (diagnosed within one month of each other) and 644 age- and gender-matched controls in Guangzhou, China. A food frequency questionnaire was used to assess habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Inverse association between the consumption of fruit and/or vegetables and hepatocellular carcinoma (HCC) was also observed in many studies, such as the European Prospective Investigation into Cancer and nutrition (EPIC) study [ 14 ], the Japan Public Health Center-based Prospective Study (JPHC study) Cohort II [ 36 ], the Shanghai Women’s and Men’s Health Studies [ 37 ] and the Hiroshima/Nagasaki Life Span Study [ 38 ]. Our previous study also showed a favorable association of dietary sources of antioxidants with PLC [ 13 ]. Moreover, there is also substantial evidence that foods rich in PUFAs, such as fish, play a role in reducing HCC risk through the anti-inflammatory effect of n-3 PUFAs on chronic hepatitis [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Inverse association between the consumption of fruit and/or vegetables and hepatocellular carcinoma (HCC) was also observed in many studies, such as the European Prospective Investigation into Cancer and nutrition (EPIC) study [ 14 ], the Japan Public Health Center-based Prospective Study (JPHC study) Cohort II [ 36 ], the Shanghai Women’s and Men’s Health Studies [ 37 ] and the Hiroshima/Nagasaki Life Span Study [ 38 ]. Our previous study also showed a favorable association of dietary sources of antioxidants with PLC [ 13 ]. Moreover, there is also substantial evidence that foods rich in PUFAs, such as fish, play a role in reducing HCC risk through the anti-inflammatory effect of n-3 PUFAs on chronic hepatitis [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 92%
“…Dietary consumption was evaluated by an interviewer-administered 79-item food frequency questionnaire (FFQ) that has been validated in previous studies [ 13 ]. All participants were required to report their intake frequency (never, per year, per month, per week, or per day) and the average amount of each food item.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results from the available data indicate that a higher consumption of fish, white meat, and grains and a lower intake of red meat and dietary sugar were associated with the reduced risk of HCC [ 4 , 7 , 35 ]. Furthermore, healthy diets are often rich in antioxidants (e.g., flavonoids, beta-carotene, vitamin C, vitamin D, and selenium), fiber, and unsaturated fatty acids, which have been observed to protect against HCC [ 4 , 36 , 37 , 38 ]. Additionally, the ratio of monounsaturated to saturated fat in the aMED and the ratio of total poly- and monounsaturated to saturated fatty acids in the HEI-2010 also showed inverse associations with HCC incidence [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study involving cell lines, it was found that acyclic retinoid (synthetic analog of retinoids) retards overexpression of Ras/Erk signaling system, thereby declining the progression of HCC [48]. In a human study, it was found that greater intake of retinol, total vitamin A, and carotenes decreases the risk of primary liver cancer at an intake of 1000 μg retinol equivalent (RE)/day or greater from food sources [49]. In another human study in the presence of hepatitis B virus, levels of dietary and serum vitamin A and β-carotene were significantly lower in HCC patients than in the control subjects [32].…”
Section: β-Carotene and Chronic Liver Diseasesmentioning
confidence: 99%